Does an Income Gap between Farm and Nonfarm Households Still Exist? The Case of the European Union. Issue 4 (2nd November 2020) - Rocchi, Benedetto; Marino, Maria; Severini, Simone
Abstract: The paper compares the income conditions of farm and nonfarm households in the whole EU and within three geographical groups of countries for the period 2008–2016. Overcoming the simple comparison of raw means of the groups, we estimate the farm/nonfarm income differentials by using Regression Adjusted and Covariate Matching techniques, which allow to control for observable characteristics among groups. Three innovative features of our analysis are that we account for the whole income of farm households (i.e. not only farm income), for the presence of in‐kind incomes from self‐consumption of produced goods and imputed rents from properties, and for the complex survey design. We find that an income differential still exists but with relevant differences across countries and along the period. Most of it is due to differences in the households' characteristics. Hence, comparing raw means of the two groups can be misleading. Nonmonetary sources of income play a not negligible role, improving the relative position of farm households. The role of agricultural and rural policy is discussed in the light of results.